2021
DOI: 10.3390/w13020117
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Charophyte Oospores in the Curonian Lagoon and their Relationship to Environmental Forcing

Abstract: Lack of knowledge about distribution of charophyte fructifications and importance of environmental conditions in the Baltic Sea coastal waters fostered us to assess the spatial-temporal patterns of oospore bank in relationship with environmental factors in the Curonian Lagoon (Lithuanian part). We mapped the distribution of oospores in 2017–2019. The importance of environmental factors was determined by the cluster analysis and boosted regression trees. Four oospores species were recorded up to 4 m depth. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Waterlogged or flooded soil can become an inhospitable environment, which excludes the majority of species, while in the remaining species, it triggers the expression of various traits and mechanisms that enable survival despite oxygen shortage in the root zone. In addition, moving water masses as waves or current present a physical factor preventing successful colonization of certain communities [7,14]. Thus, when various factors shaping the plant communities are assessed [6] according to their importance, a hydrological regime often overrides all other environmental factors, also altering the pattern of regionality, which is generally accepted in biogeography [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Waterlogged or flooded soil can become an inhospitable environment, which excludes the majority of species, while in the remaining species, it triggers the expression of various traits and mechanisms that enable survival despite oxygen shortage in the root zone. In addition, moving water masses as waves or current present a physical factor preventing successful colonization of certain communities [7,14]. Thus, when various factors shaping the plant communities are assessed [6] according to their importance, a hydrological regime often overrides all other environmental factors, also altering the pattern of regionality, which is generally accepted in biogeography [7].…”
Section: Discussionmentioning
confidence: 99%
“…Charophytes are bioindicators of ecological status in lakes and rivers, while their oospores in the sediment can be used for the reconstruction of trophic status or salinity of such ecosystems in the past. Stragauskait ė et al [14] studied the distribution and seasonal patterns of a charophyte oospore bank and its relationship with abiotic factors and charophyte stands distribution in the largest lagoon in the Baltic Sea. The study revealed that the distance of oospores from the charophyte stands, salinity, and bottom slope were environmental factors defining the distribution of charophyte fructifications.…”
Section: Main Messages Of This Special Issuementioning
confidence: 99%
“…Several last decades, the lagoon has been experiencing an increased exposure to brackish waters, nutrient loads and occurrence of the cyanobacteria blooms (Gasiunaitėet al, 2008;Vaicǐutėet al, 2021). On the other hand, there has been a significant spread of charophyte habitats in the estuarine part of the lagoon during the recent decade (especially Chara contraria) changing the submerged vegetation community dominated by pondweeds in the past (Sinkevicǐenėet al, 2017;Stragauskaitėet al, 2021).…”
Section: Introductionmentioning
confidence: 99%